AB1052 Joint Damage in Rheumatoid Arthritis Appears as Severe as Inflammation in Contempary Care at One Site, Which May Explain in Part Limitations To Treat-To-Target. (15th July 2016) - Pincus, T.; Castrejon, I.; Chua, J.; Block, J.
Abstract : Background: "Treat-to-target" should guide treatment of patients with rheumatoid arthritis (RA), with intensification of therapy if an index indicates moderate/high disease activity. However, low activity or remission are unusual in even 50% of patients. One study suggests a partial explanation, as about 20% of patients with high index scores whose therapy is not intensified had clinically important joint damage 1 . However, a quantitative estimate of the extent of joint damage is not included in quantitaive assessments of patients with RA. Objectives: To analyze quantitative physician estimates on visual analog scales (VAS) for inflammation and damage in routine care of patients with RA for the proportions of clinical management decisions which are attributable to either inflammation and/or damage. Methods: All patients seen at a one academic site complete an MDHAQ/RAPID3 at each visit, and rheumatologists complete a RheuMetric physician checklist, which includes four 0–10 VAS, for overall global estimate, inflammation or reversible disease, damage or irreversible disease, and distress or fibromyalgia, etc., explained by neither inflammation nor damage. Physicians also estimate the proportion of decisions concerning management that is attributable to inflammation, damage, or distress, totaling 100%. Cross-tabulations here were performed to analyze the proportion of clinical decisions attributable to inflammation and/or damage (not including distress), classified as low (<20%), moderate (20–60%), and severe (>60%), using chi square tests for statistical significance. Results: 110 RA patients were studied. Mean age was 56.2 (SD=17.5); 84.4% were female. Mean estimate of the physician VAS for inflammation was 2.3 (SD=2.2) and for damage was 3.1 (SD=2.2). Among the 110 patients, 29 (26%) were estimated to have clinical decisions based on high inflammation, while 39 (35%) were estimated to have high damage (Table). A high level of inflammation and low level of damage was estimated in 19 patients (22% of all patients), while a high level of damage and low level of inflammation was estimated in 27 patients (35% of all patients). Conclusions: Damage appears to impact clinical decisions in current treatment of patients with RA as much as inflammation. Structural damage is unlikely to be ameliorated by aggressive medical therapy, and these data may explain in part why clinical trials of established patients indicate only 60% ACR20 responses with all 10 approved biological agents for RA. Moreover, the data may explain in part why fewer patients are in remission than might be expected using a "treat-to-target" strategy. Estimates of inflammation, damage and distress are feasibly completed by rheumatologists in busy clinical settings, and may help clarify and document decisions concerning therapies and outcomes. References: Tymms K, et al. Arthritis Care Res (Hoboken). 2014;66:190–6. Disclosure of Interest: None declared